An educational method for evaluating the resistance to the treatment in the diagnosis of dyscalculia - Giampaolo Chiappini; Giacomo Cozzani; Shaula Verna; Cristina Potente; Fabrizio De Carli (Firenze University Press, 2016)
In this paper a didactical method that has been proven effective for evaluating the "resistance to the treatment" of the student is presented. This parameter is essential for distinguishing the learning difficulties in mathematics from the learning disorder of dyscalculia. The method is based on GimmeFive, an application that has been designed to develop skills in mental calculation of multi-digit additions and subtractions. In this paper we present the results of two experiments conducted with groups of students respectively with learning difficulties in mathematics and dyscalculia. These experiments allowed to show the effectiveness of the didactical method in the evaluation of the resistance to the treatment and to discuss the features that make it adequate for the evaluation of the learning disorder.   An educational method for evaluating the resistance to the treatment in the diagnosis of dyscalculia In questo lavoro viene presentato un metodo didattico che si è dimostrato efficace per valutare la resistenza al trattamento dello studente che è uno dei parametri fondamentali per distinguere la difficoltà di apprendimento in matematica dal disturbo di apprendimento noto come discalculia. Il metodo si basa sull'uso dell'applicazione GimmeFive che è stata progettata per sviluppare competenze nel calcolo mentale di addizioni e sottrazioni a più cifre. In questo lavoro vengono presentati risultati di due sperimentazioni condotte con gruppi di studenti rispettivamente con difficoltà di apprendimento e con diagnosi di discalculia. Queste sperimentazioni hanno consentito di mostrare l'efficacia del metodo didattico nella valutazione della resistenza al trattamento e di discutere le caratteristiche che lo rendono adeguato per la valutazione del disturbo di apprendimento.